Effects of Different Protocols of Low-Level Laser Therapy on Collagen Deposition in Wound Healing - Cunha,John Lennon Silva (2019)
Abstract The low-level laser has proven successful in stimulating the production of collagen in wound healing assays. However, diversity has been observed in the protocols used. This work has evaluated the effects of three protocols of low-level laser therapy (LLLT) in the healing of open wounds in rats. Standard-sized wounds of 1 cm2 were performed with a scalpel in the middorsal region of 60 male Wistar rats weighing 225±25 g, and they were assigned into four groups (n=15): CTR (non-irradiated animals), LT1 (20 J/cm2 daily), LT2 (16 J/cm2 daily) and LT3 (20 J/cm2 daily). After 7, 14 and 21 days, five animals/day were euthanized and the wounds analyzed histologically. Data were subjected to normality analysis of distribution using Shapiro-Wilk test. Gaussian data were analyzed using ANOVA and Bonferroni tests whereas non-Gaussian data were analyzed using Kruskal-Wallis and Dunn tests, considering significant p values less than 0.05. The LLLT in all protocols reduced the inflammation and collagen deposition increased significantly (p<0.05). However, LT2 showed the highest levels of collagen in all phases of the study (p<0.05) induced faster replacement of immature collagen III by mature collagen I in the early stages of repair and early collagen remodeling promoted by providing better organization architectural beams deposited. It was concluded that all protocols induced an increase in collagen scar. However, the protocol 2 (16 J /cm2, daily application) promoted the most significant increases in collagen deposition, accelerated maturation of collagen and showed the best architecture of the final fibrous scarring.